Effect of Dissolved Oxygen and Chemical Scarification on Andrographis paniculata Seed Germination in Macrobubble Conditions - Athakorn Promwee; Shams Shaila Islam; Thanet Khomphet (International Journal of Agronomy)
Andrographis paniculata is used in Thai traditional medicine. This plant contains a bitter compound called andrographolide, which is highly effective in the prevention of many diseases. It is an effective treatment for infectious diseases and has a prophylactic effect owing to its powerful immunity-boosting benefits. Recently, it has been widely used to treat COVID-19. However, commercial planting of A. paniculata is performed by seeding, which leads to seed germination problems. The seed germination is relatively low and not efficient under normal conditions for various reasons, such as a combined dormancy of physical and innate nature, the diversity of the seeds in different lots, and the fact that the germination duration was not uniform in the same lot. An easily applied and inexpensive method for farmers to develop mass plantings to stimulate germination is by using macrobubble conditions by aerating seeds in sterile water in collaboration with chemical scarification, which is the idea of creating a hard seed coat that causes seed dormancy to break while root germination occurs at 25°C. Germination was completed after 16 days. The dissolved oxygen (DO) concentrations in this environment were 5, 6, 7, 8, and 9 mg·L−1. The oxygen intensity of 9 mg·L−1 showed the highest germination percentage (26.33%). It was found to be optimal for macrobubble conditions. Seedlings were treated with chemicals (PEG, NaCl, H2SO4, KCl, KNO3, NaHClO3, and GA3) after soaking in macrobubbles with optimum DO. The results showed that NaHClO3 conc. (30 min) showed a generation percentage reaching 92%, which could greatly promote up to 3.63 folds compared with the control in the macrobubble aeration system.